Recent history of metal contamination in the Fangcheng Bay (Beibu Gulf, South China) utilizing spatially-distributed sediment cores: Responding to local urbanization and industrialization. (September 2020) - Yu, Xiaoxiao; Zhang, Zhiwei; Feng, Aiping; Gu, Dongqi; Zhang, Rui; Xia, Peng; Yan, Wenwen; Zhou, Xiangjun
Abstract: In this study, the recent history of heavy metal pollution in the Fangcheng Bay (South China) was reconstructed utilizing three 210 Pb-dated sediment cores. The metal concentration profiles display three trends since the 1970s and clearly reflect local urbanization and industrialization. The metals in the Fangcheng Bay started to accumulate in the 1970s but remained relatively low until the 1990s which corresponds to the slow urbanization and industrialization. The metal accumulation in the eastern Fangcheng Bay peaked in the early 2000s following the steep increases in accordance with the rapid industrialization of the eastern Fangcheng Bay where the core HSL was collected. Conversely, the heavy metal profiles in the western Fangcheng Bay present slight step increases in the early 2000s followed by a dramatic metal enrichment in the late 2000s; the expansion of these two cores, which begins in the early 2000s, concurs well with the rapid local urbanization and industrialization. Highlights: Heavy metal contamination of the Fangcheng Bay corresponds well to local urbanization and industrialization. The slight heavy metal accumulation between 1970 and 2000 matches with the slow industrialization. The dramatic heavy metal accumulation coincides with the rapid urbanization and industrialization happened in the 2000s. The quality of sediments in the Fangcheng Bay is acceptable for marine ecosystems.